2018
DOI: 10.3390/molecules23010207
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Binding Affinities of Water-Soluble Calixarenes with the Organophosphorus Nerve Agent Soman (GD) and Commonly-Used Nerve Agent Simulants

Abstract: The formation of inclusion complexes of the water-soluble p-sulfonatocalix[n]arenes, where n = 4 or 6, with the Chemical Warfare Agent (CWA) GD, or Soman, and commonly used dialkyl methylphosphonate simulants has been studied by experimental solution NMR methods and by Molecular Mechanics (MMFF) and semi-empirical (PM6) calculations. Complex formation in non-buffered and buffered solutions is driven by the hydrophobic effect, and complex stoichiometry determined as 1:1 for all host:guest pairs. Low affinity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Here, we identify three trends, one for the phosphoryl species and two for the sulfonyl species. The two trends identified for the sulfonyl species correspond to the two different classes of sulfonate molecules present within the library of simulants studied, those substituted with a toluene group (16)(17)(18)(19)(20) and those substituted with a methyl group (21)(22)(23)(24)(25)(26). As the limitation of the experimental association constant determination methodology is ≈10 M −1 , we suggest that any values incorporating ≤10 M −1 may be considered inappropriate when included into a model such as this and should be treated with caution.…”
Section: Single Parameter Predictive Modelsmentioning
confidence: 89%
See 2 more Smart Citations
“…Here, we identify three trends, one for the phosphoryl species and two for the sulfonyl species. The two trends identified for the sulfonyl species correspond to the two different classes of sulfonate molecules present within the library of simulants studied, those substituted with a toluene group (16)(17)(18)(19)(20) and those substituted with a methyl group (21)(22)(23)(24)(25)(26). As the limitation of the experimental association constant determination methodology is ≈10 M −1 , we suggest that any values incorporating ≤10 M −1 may be considered inappropriate when included into a model such as this and should be treated with caution.…”
Section: Single Parameter Predictive Modelsmentioning
confidence: 89%
“…It is therefore vital to consider the appropriate properties of any simulant chosen to aid in the development of novel OP CWA detection, decontamination, or remediation methodologies. [21][22][23][24] Recently, work undertaken by Snurr and Mendonca, has shown that density functional theory (DFT) can be used to study the mechanism of OP hydrolysis, which has resulted in the development of a quantitative structure activity relationship (QSAR) model that enables the identification of appropriate OP CWA simulants for decontamination purposes. 25 However, when considering supramolecular technologies, the moiety target is often selective coordination of the polar PvO functionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sambrook and co‐workers studied also the ability of p ‐sulfonatocalix[n]arenes (n=4 and 6) to recognize Soman in water [72] . Binding affinity values, calculated by NMR titrations, are low with both calixarene derivatives (calix‐4 shows a K=75 M −1 , while calix‐6 shows a K=10 M −1 ).…”
Section: Sensing By Supramolecular Approachmentioning
confidence: 99%
“…12 Since calixarenes can be modified by different functionalization at the lower and/or upper rims of the molecule, the calixarene derivatives provide useful platforms for anchoring a variety of binding units for ions and neutral molecules, and incorporating functional groups, such as ester, ether, ketone, amide, and carboxylic acid groups, exhibit excellent binding abilities. [13][14][15][16] Their structures have unique three-dimensional surface, which correspondence: ramin Karimian chemical Injuries research center, systems Biology and Poisonings Institute, Baqiyatallah University of Medical sciences, Mollasadra street, sheykh Baha'i street, Tehran 1435915371, Iran Tel +98 912 610 1850 email karimian.r@gmail.com made them as one of the best-known host molecules and used in the biomedical applications of supramolecular systems based on host-guest interactions. 17,18 A particular interest was generated by the possibility of using calixarenes as vehicles in drug delivery and other pharmacological contexts.…”
Section: Introductionmentioning
confidence: 99%